Integrating Animal-Assisted Therapy Into TF-CBT for Abused Youth With PTSD: A Randomized Controlled Feasibility Trial. (August 2022) - Allen, Brian; Shenk, Chad E.; Dreschel, Nancy E.; Wang, Ming; Bucher, Ashley M.; Desir, Michelle P.; Chen, Michelle J.; Grabowski, Simonie R.
This clinical trial examined animal-assisted therapy (AAT) as an adjunct to Trauma-Focused Cognitive-Behavioral Therapy (TF-CBT) for abused youth with posttraumatic stress disorder (PTSD). Youth between the ages of 6 and 17 ( M = 11.79, SD = 3.08) were randomized to receive standard TF-CBT or TF-CBT with adjunctive AAT (TF-CBT+AAT) employing retired service dogs. Feasibility metrics evaluating the addition of AAT were collected in addition to common clinical outcomes evaluated in TF-CBT trials. The inclusion of AAT increased the number of potential participants who declined participation and there were no noted benefits for treatment retention or satisfaction with services. Analyses showed that the inclusion of AAT did not enhance improvement of PTSD symptom severity (β = .90, t = .94, p = .351) or a number of other outcomes. On the contrary, there were indications from analyses and clinician feedback that AAT may have attenuated improvement in many cases. This study identified a number of important feasibility considerations in the design of studies testing AAT. However, the results examining clinical outcomes suggest that the inclusion of AAT with TF-CBT in the treatment of maltreated youth with PTSD is not warranted at this time.